Opens Typology Architecture Of Islam (Case Study : Bayt Al Qur’an And Museum Istiqlal) - Wahid, Julaihi; Alamsyah, Bhakti (2008)

(untitled)
Progress of technology that is increasingly fast more enablingly man to innovate in finding a new findings, do not aside from in architecture area.